2011
DOI: 10.1016/j.jcta.2011.02.010
|View full text |Cite
|
Sign up to set email alerts
|

The chromatic number of almost stable Kneser hypergraphs

Abstract: International audienceLet V(n,k,s) be the set of k-subsets S of [n] such that for all i,j∈S, we have |i−j|⩾s. We define almost s-stable Kneser hypergraph View the MathML source to be the r-uniform hypergraph whose vertex set is V(n,k,s) and whose edges are the r-tuples of disjoint elements of V(n,k,s). With the help of a Zp-Tucker lemma, we prove that, for p prime and for any n⩾kp, the chromatic number of almost 2-stable Kneser hypergraphs View the MathML source is equal to the chromatic number of the usual Kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 14 publications
1
81
0
Order By: Relevance
“…There are also various generalizations of Tucker's lemma. The next lemma is a combinatorial variant of the Z p -Tucker lemma proved and modified in [35] and [24], respectively.…”
Section: Tucker's Lemma and Its Generalizationsmentioning
confidence: 99%
See 3 more Smart Citations
“…There are also various generalizations of Tucker's lemma. The next lemma is a combinatorial variant of the Z p -Tucker lemma proved and modified in [35] and [24], respectively.…”
Section: Tucker's Lemma and Its Generalizationsmentioning
confidence: 99%
“…As an approach to Conjecture A, Meunier [24] showed that χ(KG r (n, k) ∼ 2−stab ) = n−r(k−1) r−1 and he strengthened the above conjecture as follows.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Indeed, Dold's theorem implies that if there is such a map λ, then m ≥ n. It is worth noting that the idea of using Dold's theorem or some of it specializations such as the Z p -Tucker lemma has been used in several articles initiated by a fascinating paper of Matoušek [17]. For instance, see [1,4,6,7,12,18,19,24]. Usually, the most challenging task in using Dold's theorem is how to define the map λ, especially the sign part s(X).…”
Section: Notations and Toolsmentioning
confidence: 99%